Robo Banking in India: Transforming the Future of Financial Services - Dr. S. Ramesh (HM Journals, 2023)
Robo banking, a revolutionary technological advancement, has disrupted the traditional banking landscape in India. This article explores the concept of robo banking, its impact on the financial services industry, and its potential implications for customers and the banking sector. The study reviews existing literature on robo banking, its benefits, challenges, and regulatory framework. The discussion delves into how robo banking has improved customer experience, enhanced financial inclusion, and increased operational efficiency. The article concludes with an analysis of the future prospects of robo banking in India and its role in shaping the banking sector.